2010
DOI: 10.1111/j.1365-2095.2009.00647.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of forage fish and dietary lipid supplements on egg quality and fry production in channel catfish (Ictalurus punctatus) × blue catfish (Ictalurus furcatus) hybridization

Abstract: Hybrid catfish (channel catfish Ictalurus punctatus × blue catfish Ictalurus furcatus) display characteristics that are favourable to aquaculture production. Low hatch percentages are a principal reason this hybrid is not used widely in the catfish industry. This study was conducted to determine whether additional food source rich in lipids may lead to a higher quality egg production. A 10‐week feed trial was conducted in ponds in Auburn, AL. A total of 219 female Kansas Select channel catfish were stocked int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…For spectroscopic measurements, saline solution (0.85%) served as blank solution and serial dilutions were prepared of 10 7 , 5 × 10 6 , 2.5 × 10 6 ; 1.25 × 10 6 , 0.625 × 10 6 cells mL −1 . The sperm concentration of blue catfish in the samples were estimated with a Thermo Scientific Genesys 20 spectorophotometer (Fisher Scientific, Madison, WI, USA) at 546 nm based on the methods previously described by Dong, Eudeline, Huang & Tiersch ; Durland, Quintero, Davis & Dunham . A linear relationship between sperm concentration and optical density (OD) was observed and the regression equation was y = 12205652 × OD − 770179 ( r = 0.96, P < 0.05).…”
Section: Methodsmentioning
confidence: 99%
“…For spectroscopic measurements, saline solution (0.85%) served as blank solution and serial dilutions were prepared of 10 7 , 5 × 10 6 , 2.5 × 10 6 ; 1.25 × 10 6 , 0.625 × 10 6 cells mL −1 . The sperm concentration of blue catfish in the samples were estimated with a Thermo Scientific Genesys 20 spectorophotometer (Fisher Scientific, Madison, WI, USA) at 546 nm based on the methods previously described by Dong, Eudeline, Huang & Tiersch ; Durland, Quintero, Davis & Dunham . A linear relationship between sperm concentration and optical density (OD) was observed and the regression equation was y = 12205652 × OD − 770179 ( r = 0.96, P < 0.05).…”
Section: Methodsmentioning
confidence: 99%
“…For example, they investigated the interaction of feed quality and feeding frequency (Quintero et al, ) and dietary lipid sources (Quintero, Durland, Davis, & Dunham, ) on female channel catfish's reproductive performance with regard to improving hybridization. In addition, the effects of forage fish and dietary lipid on egg quality and fry production in hybridization between channel catfish and blue catfish were studied (Durland, Quintero, Davis, & Dunham, ). Other studies were conducted on the effects of feed additives on mucosal health and disease resistance (Zhao et al, ), the contribution of natural food sources in pond waters to xanthophyll found in fillets (Hu, Roy, & Davis, ), and on the use of supplemental lysine in practical feeds (Nguyen & Davis, ).…”
Section: To Presentmentioning
confidence: 99%
“…Fry require higher-protein diets compared with fingerlings and grow-out fish. Additionally, brood fish require more nutritious diets (protein, fish meal, fatty acids, vitamins) a few months before spawning begins (35,46,47), whereas during the rest of the year, they can be fed the regular 32% protein diet.…”
Section: Nutrition and Feedingmentioning
confidence: 99%